Reduced social participation among seniors with self-reported visual impairment and glaucoma. - Shicheng Jin; Graham E Trope; Yvonne M Buys; Elizabeth M Badley; Kednapa Thavorn; Peng Yan; Harrish Nithianandan; Ya-Ping Jin (PLoS ONE, 2019)
Objective Social participation benefits health. We assessed the relationship between self-reported visual impairment (VI) and glaucoma versus seniors' social participation. Methods Data from individuals aged ≥65 years responding to the Canadian Community Health Survey Healthy Aging 2008/2009 (n = 16,369) was analyzed. Participation in eight social activities by seniors with and without self-reported VI or glaucoma was compared. Results Seniors with VI had significantly reduced participation (p<0.05) in sports/physical activities (18.0% vs. 33.6%), family/friendship activities outside the household (39.7% vs. 53.0%), service club/fraternal organization activities (11.4% vs. 18.4%), volunteer/charity work (13.4% vs. 24.9%), educational/cultural activities (16.2% vs. 24.5%), and other social recreational activities (21.6% vs. 31.0%) compared to those without VI. Differences in participation in church/religious activities (40.6% vs. 44.5%) and community/professional association activities (15.3% vs. 18.0%) were non-significant between seniors with and without VI. Seniors with glaucoma versus those without had significantly reduced participation (p<0.05) in family/friendship activities (46.6% vs. 52.9%), sports/physical activities (26.0% vs. 33.6%) and volunteer/charity work (20.4% vs. 24.9%). No participation in any social activity was significantly higher among seniors with VI versus those without (10.1% vs. 2.9%, p<0.05), but was similar among seniors with and without glaucoma (3.9% vs. 3.1%, p>0.05). After adjusting for the effects of age, sex, education, household income, ethnicity, job status and chronic diseases (adjusted odds ratio, aOR = 3.4 (95% confidence interval (CI) 2.0-5.8), seniors with VI but no glaucoma were more likely not to engage in any social activities compared to seniors without VI and no glaucoma. Seniors with glaucoma but without VI had a similar level of non-participation (aOR = 0.9, 95%% CI 0.5-1.7). Conclusions Significantly reduced social participation was found across six community activities among seniors with self-reported VI and in three activities among those with self-reported glaucoma. Policies and programs that help seniors with VI or glaucoma engage in social activities are needed.